Upacara Ngerebong di Pura Agung Petilan Desa Adat Kesiman - Ni Made Odi Tresna Oktavianti (Journal Social and Humaniora, 2021)
Ngerebong ceremony is an oral tradition which is interpreted as a sacred ritual for the people in the Kesiman Traditional Village, Denpasar City. The Ngerebong ceremony is held every six months, to be precise every eight days after Kuningan Day. Until now, the Ngerebong ceremony which involves many parties and cultural components is still carried out by the Kesiman Traditional Village community. This is a challenge for the people of the Kesiman Traditional Village who do not shut themselves off from the influence of modernization. The purpose of this research was carried out to find out and understand the problems associated with the implementation of the Ngerebong ceremony for the people of the Kesiman Traditional Village. The research, which is located in the Kesiman traditional village, was conducted using qualitative methods and analyzed using the habitus theory. The problems studied include (1) what factors cause changes in the implementation of the Ngerebong ceremony?; (2) what is the function of the Ngerebong ceremony for the people of the Kesiman Traditional Village?; (3) what are the implications of the Ngerebong ceremony for the people of Denpasar City? The results showed that (1) the people of the Kesiman Traditional Village saw that they had to continue to carry out the Ngerebong ceremony because in their life it was motivated by religious ideology, conservation ideology, power ideology, and cultural ideology that made them obey the traditions they already had; (2) along with the times, the people of the Kesiman Traditional Village carry out the Ngerebong ceremony lively but still in accordance with the stages, traditions and customs they already have; (3) the implications of the implementation of the Ngerebong ceremony in the current global era for the people of the Kesiman Traditional Village appear to directly touch the characteristics of their life, strengthening the quality of cultural values ??and togetherness for all people in facing the challenges of cultural change in the global era.